Peningkatan Kemampuan Komunikasi Dan Pemecahan Masalah Matematika Dengan Pembelajaran Berbasis Masalah - Ernastin, Wiba Dwi, Rita P. Khotimah, S.Si., M.Sc (2015)
This research aims to improve communication skills and problem solving math class VII MTs Negeri Filial Pulutan, Boyolali with problem based learning. This research includes the type of action research class. The subjects in this study is the teacher as the giver of action and grade VII/A totalling 25 students as the recipient of the action. Methods of data collection include observation, fieldnotes, interview, tests, and documentation. Data analysis techniques include the reduction of the data, the presentation of data, and the withdrawal of the conclusion. For the validity of the data used the technique of triangulation. Data results showed an increase in mathematical communication skills can be seen from 1) Ability to express mathematical ideas from (12,64%) became (81,30%); 2) Ability to evaluate mathematical ideas verbally and in writing from (12,53%) became (72,01%); 3) The ability of the States situation into mathematical models from (14,53%) became (62,34%). An increase in mathematical problem solving ability can be seen from 1) Ability to understand issues, from (36,64%) became (85,43%); 2) Capabilities of the planned settlement, from (20,23%) became (79,42%); 3) Ability to resolve problems according to plan, an increase of (11,53%) into (69,42%); 4) capability checked against all the increased from (13,53%) becoming (57,42%). Thus it can be concluded that the use of problem based learning can improve communication skills and problem solving of mathematics students.